Unplanned hospitalisations among subsidised nursing home residents in Singapore: Insights from a data linkage study - Weiren Charles Quah; Chin Jong Leong; Edward Chong; James Alvin Low; Heidi Rafman (Annals, Academy of Medicine, Singapore)
Introduction: Hospitalisations can pose hazards and may not be an appropriate care setting for frail nursing home (NH) residents. Few studies have quantified the extent of NH resident hospitalisations in Singapore, hence we aimed to address this knowledge gap by studying characteristics of unplanned hospitalisations over a 1-year period. Method: This was a retrospective cohort study of 9922 subsidised residents across 59 NHs in Singapore, with analysis using administrative healthcare data. Key measures included inpatient admission and emergency department visit rates, final discharge diagnoses and estimated costs. We examined correlates of inpatient admissions with a multivariable zero-inflated negative binomial regression model incorporating demographics, institutional characteristics and Charlson Comorbidity Index. Results: There were 6620 inpatient admissions in 2015, equivalent to 2.23 admissions per 1000 resident days, and the majority were repeat admissions (4504 admissions or 68.0%). Male sex (incidence rate ratio [IRR] 1.23), approaching end-of-life (IRR 2.14), hospitalisations in the past year (IRR 2.73) and recent NH admission within the last 6 months (IRR 1.31–1.99) were significantly associated with inpatient admission rate. Top 5 discharge diagnoses were lower respiratory tract infections (27.3%), urinary tract infection (9.3%), sepsis (3.1%), cellulitis (1.9%) and gastroenteritis (1.1%). We estimated the total system cost of admissions of subsidised residents to be SGD40.2 million (USD29.1 million) in 2015. Conclusion: We anticipate that unplanned hospitalisation rate will increase over time, especially with an increasing number of residents who will be cared for in NHs. Our findings provide a baseline to inform stakeholders and develop strategies to address this growing problem.